Kara Erik Çağala - Bircan, Zekeriyya (Fırat University, 2014)
Harput’s music has a private and important place in the Turkish music.Kursubashı in winter months, weddings in summer months, rock and poolside venues are places where Harput songs are performed. People living in Harput and in its surrounding have written poems to describe their feelings towards different events taking place around them. As a result of this, they have produced many songs. Those songs have been passed down from generation to generation and become part of the traditional folk music. Moreover, there are songs whose composers are known ‘‘Kara Erik Çağala’’ (Black Plum Raw) is one of the songs of this type. This paper aims at explaining the birth of this song

Harput musikisi, Türk musikisi içerisinde özel ve önemli bir yere sahiptir. Kış aylarında kürsübaşları, yaz aylarında düğünler, kaya ve havuz başları Harput türkülerinin dile getirildiği başlıca mekânlardır. Harput ve çevresinde yaşayan insanlar çeşitli olaylar karşısında duygularını şiire dökerek seslendirmişler, bunun sonucu olarak da çok sayıda türkü meydana getirmişlerdir. Bunlar dilden dile dolaşarak zamanla anonim halk müziği ürünleri haline gelmiştir. Bununla birlikte, bestekârı meçhul olmayan Harput türküleri de vardır. İşte “Kara Erik Çağala” Harput’un bu çeşit türkülerden biri olup, bu yazıda onun doğuş öyküsü anlatılmaktadır
KARA ERİK ÇAĞALA